Strengths, resources or controls?: The assessment of protective factors in probation practice - Whyman, Rob (Probation journal, 2019)
This article is based on research that explored how well protective factors are understood, assessed and used in risk assessment within probation practice. The research was facilitated by the Sir Graham Smith Award, administered by the Probation Institute. Semi-structured interviews explored the knowledge, ability, confidence and attitudes of a sample of probation officers working in the National Probation Service. The findings suggest that understanding of the term is varied, and there are some limitations around knowledge, but that attitudes towards protective factors are positive and there is some good practice in terms of assessment.